Design of Immersive Museum Experiences: Improving Visitor Engagement through Co-Creation, Augmented Reality and Gamification - Mariana Leitão Fernandes de Morais Sarmento (2024)
The use of immersive experiences and extended reality (XR) in museums is becoming increasingly prevalent as a means of enhancing visitor engagement. This study examines the use of augmented reality (AR) to develop interactive, recurring museum experiences that facilitate engagement with cultural heritage. The study employs a design-based research (DBR) methodology with co-creation, focusing specifically on the Museu Nacional Soares dos Reis and the development of an AR application, 'ARtefacto'. The latter incorporates gamified activities with the objective of promoting visitor engagement with the museum space, the artefacts and the content. The involvement of a diverse range of stakeholders in co-creation ensured that the application was accessible and tailored to different users, in line with the museum's mission. Furthermore, the study explores a gamified outdoor experience, developed with the KLUEST platform, which aims to extend engagement beyond the physical space of the museum. The results of the user testing indicate that the key factors influencing acceptance are ease of use, perceived value, and alignment with the educational objectives. The research reveals that the application of participatory methodology in the development of immersive museum experiences can improve cultural connections, promote socialisation and optimise the impact of museums.